Clinical and psychopathological features of the course and outcome of the first psychotic episode - Kosovsky , V. (Journal of Education, Health and Sport, 2024)
The article presents the results of the study of the clinical-anamnestic, clinical-psychopathological and clinical-dynamic features ofthefirst psychotic episode (FPE), taking into account the nosological specificity. It was determined that FPE (F20) is characterized by an early onset and significant duration of the prodrome (more than 3 years), the presence in the clinical picture of a moderate level of negative symptoms (apato-abulous symptoms, manifestations of flattening and rigidity of affect and austic tendencies). FPE (F23) defines the shortest (up to 3 months) prodromal period, the presence in the clinical picture of excitement and anxiety of a high and moderate level, disorganization and physical tension. FPE (F25) is characterized by a rather long prodrome (from 3 months) with manifestations in the form of emotional disorders, the presence in the clinical picture of pronounced symptoms of excitement, depression, anxiety, physical tension and impulsivity, negative symptoms in the form of apatho-abolic manifestations and anhedonia - asociality. According to indicators of the dynamics of the condition of patients with FPE, an unfavorable prognosis for recovery at F20 was determined.